Confronting the anxiety of Generation Z: electroacupuncture therapy regulates oxidative stress and microglia activity in amygdala-basolateral of socially isolated mice - Yin, Tong; Yuan, Junyun; Liu, Lu; Wang, Yinxin; Lin, Yuanfang; Ming, Kangwen; Lv, Hang (Frontiers in Psychiatry, 2025)
IntroductionAnxiety disorders are prevalent mental health conditions characterized by significant impairments in daily functioning and social interactions. Despite the effectiveness of pharmacological treatments, challenges such as medication resistance, adverse side effects, and the high rate of relapse necessitate the exploration of alternative therapies. Recently, electroacupuncture (EA) has garnered attention as a promising non-pharmacological intervention for anxiety disorders; however, the mechanisms by which EA exerts its anxiolytic effects remain poorly understood. This study aims to elucidate the role of microglial cells in anxiety, specifically examining how EA modulates microglial morphology and function within the basolateral amygdala (BLA) in the context of anxiety induced by social isolation.MethodsUtilizing a mouse model of social isolation-induced anxiety, we evaluated anxiety-like behaviors through the Elevated Plus Maze (EPM) and Open Field Test (OFT). Additionally, biochemical analyses and immunofluorescence imaging were performed to assess the expression of NADPH oxidase 2 (NOX2), microglial activation markers, and levels of oxidative stress.ResultsOur findings reveal that EA treatment significantly mitigates anxiety-like behaviors in mice, correlating with a reduction in NOX2 expression within BLA microglia and decreased levels of reactive oxygen species (ROS). Furthermore, EA was observed to restore normal microglial morphology, indicating its potential role in modulating microglial activity.DiscussionThe results of this study suggest that EA exerts its anxiolytic effects through the modulation of oxidative stress and the activity of microglia in the BLA. These findings provide new insights into the cellular mechanisms underlying the therapeutic effects of EA, highlighting the potential for non-pharmacological strategies in the management of anxiety disorders and paving the way for future research aimed at improving clinical outcomes for individuals suffering from anxiety.